American Association for the Surgery of Trauma/American College of Surgeons-Committee on Trauma Clinical Protocol for inpatient venous thromboembolism prophylaxis after trauma. Issue 3 (March 2022) - Yorkgitis, Brian K.; Berndtson, Allison E.; Cross, Alisa; Kennedy, Ryan; Kochuba, Matthew P.; Tignanelli, Christopher; Tominaga, Gail T.; Jacobs, David G.; Marx, William H.; Ashley, Dennis W.; Ley, Eric J.; Napolitano, Lena; et al.
Abstract : ABSTRACT: Trauma patients are at increased risk of venous thromboembolism (VTE), which includes both deep vein thrombosis and pulmonary embolism. Pharmacologic VTE prophylaxis is a critical component of optimal trauma care that significantly decreases VTE risk. Optimal VTE prophylaxis protocols must manage the risk of VTE with the competing risk of hemorrhage in patients following significant trauma. Currently, there is variability in VTE prophylaxis protocols across trauma centers. In an attempt to optimize VTE prophylaxis for the injured patient, stakeholders from the American Association for the Surgery of Trauma and the American College of Surgeons-Committee on Trauma collaborated to develop a group of consensus recommendations as a resource for trauma centers. The primary goal of these recommendations is to help standardize VTE prophylaxis strategies for adult trauma patients (age ≥15 years) across all trauma centers. This clinical protocol has been developed to (1) provide standardized medication dosing for VTE prophylaxis in the injured patient; and (2) promote evidence-based, prompt VTE prophylaxis in common, high-risk traumatic injuries. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level V. Abstract : Supplemental digital content is available in the text.